Daughter Preference and Contraceptive-use in Matrilineal Tribal Societies in Meghalaya, India (Journal of Health, Population and Nutrition, 2013)
Although son preference in patrilineal society is an established fact, daughter preference in matrilineal society is not thoroughly examined. Very few studies have been carried out on the issue. This paper attempts to explore the daughter preference and contraceptive-use in matrilineal tribal societies in Meghalaya, India. Data from the National Family Health Survey 1998-1999 have been used in this study because, among the large-scale surveys, only this dataset allows identification of matrilineal sample. Mean, percentage, and standard deviation are computed in the present study. Further, the data have been cross-tabulated, and logistic regression has been run through SPSS (version 15). Among the ever-married matrilineal women, 17% desired more sons than daughters but 18.2% desired more daughters than sons. About 11% of ever-married women could achieve their desired sex composition of children. However, a very striking finding suggests that, even after achieving desired sex composition of children, as high as 61.8% of women were still not using contraception mainly because of programme factors while one-fourth were still depending on temporary methods. The rest 13.2% adopted terminal method of contraception, which calls for immediate attention of planners. With the increase in the number of sons but without daughter, contraceptive-use drastically decreased. The most desired sex composition of children seems to be two daughters and a son. Absence of daughter with increase in the total number of sons increased the desire for additional children. Every woman with two or more sons but without daughter wanted the next child to be a daughter. Thus, there are ample evidences to draw the conclusion that there is, in fact, a daughter preference in the matrilineal tribal societies in Meghalaya, India. Policy-makers may, thus, target the women who have achieved fertility and should ensure that daughter preference does not lead to the negligence to sons. J HEALTH POPUL NUTR 2013 Jun; 31(2): 278-289 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16393